Adaptive control of a jet turboshaft engine driving a variable pitch propeller using multiple models. (August 2017) - Ahmadian, Narjes; Khosravi, Alireza; Sarhadi, Pouria
Highlights: In this paper, a new strategy as second level adaptation is extended to control a turboshaft engine. The JetCat SPT5 turboshaft engine concludes various operating points. Important operating points of idle, cruise and full thrust are designed as identification models. Also the stability analysis of the proposed method is introduced. Second level adaptation is compared with two conventional first level adaptation using a single model and model reference adaptive control strategies. The performance and fidelity of this method is approved via simulation studies. Abstract: In this paper, a multiple model adaptive control (MMAC) method is proposed for a gas turbine engine. The model of a twin spool turbo-shaft engine driving a variable pitch propeller includes various operating points. Variations in fuel flow and propeller pitch inputs produce different operating conditions which force the controller to be adopted rapidly. Important operating points are three idle, cruise and full thrust cases for the entire flight envelope. A multi-input multi-output (MIMO) version of second level adaptation using multiple models is developed. Also, stability analysis using Lyapunov method is presented. The proposed method is compared with two conventional first level adaptation and model reference adaptive control techniques. Simulation results for JetCat SPT5 turbo-shaft engine demonstrate the performance and fidelity of the proposed method.